Venous thromboembolism in orthopaedic oncology: risk factors, incidence, and prophylaxis. (1st December 2020) - Lex, Johnathan R.; Evans, Scott; Cool, Paul; Gregory, Jonathan; Ashford, Robert U.; Rankin, Kenneth S.; Cosker, Tom; Kumar, Amit; Gerrand, Craig; Stevenson, Jonathan; ,
Abstract : Aims: Malignancy and surgery are risk factors for venous thromboembolism (VTE). We undertook a systematic review of the literature concerning the prophylactic management of VTE in orthopaedic oncology patients. Methods: MEDLINE (PubMed), EMBASE (Ovid), Cochrane, and CINAHL databases were searched focusing on VTE, deep vein thrombosis (DVT), pulmonary embolism (PE), bleeding, or wound complication rates. Results: In all, 17 studies published from 1998 to 2018 met the inclusion criteria for the systematic review. The mean incidence of all VTE events in orthopaedic oncology patients was 10.7% (1.1% to 27.7%). The rate of PE was 2.4% (0.1% to 10.6%) while the rate of lethal PE was 0.6% (0.0% to 4.3%). The overall rate of DVT was 8.8% (1.1% to 22.3%) and the rate of symptomatic DVT was 2.9% (0.0% to 6.2%). From the studies that screened all patients prior to hospital discharge, the rate of asymptomatic DVT was 10.9% (2.0% to 20.2%). The most common risk factors identified for VTE were endoprosthetic replacements, hip and pelvic resections, presence of metastases, surgical procedures taking longer than three hours, and patients having chemotherapy. Mean incidence of VTE with and without chemical prophylaxis was 7.9% (1.1% to 21.8%) and 8.7% (2.0% to 23.4%; p = 0.11), respectively. No difference in the incidence of bleeding or wound complications between prophylaxis groups was reported. Conclusion: Current evidence is limited to guide clinicians. It is our consensus opinion, based upon logic and deduction, that all patients be considered for both mechanical and chemical VTE prophylaxis, particularly in high-risk patients (pelvic or hip resections, prosthetic reconstruction, malignant diagnosis, presence of metastases, or surgical procedures longer than three hours). Additionally, the surgeon must determine, in each patient, if the risk of haemorrhage outweighs the risk of VTE. No individual pharmacological agent has been identified as being superior in the prevention of VTE events. Cite this article: Bone Joint J 2020;102-B(12)1743:–1751.